Análisis del crecimiento e incremento de cinco pináceas de los bosques de Durango, México - Corral R., Sacramento; Návar Cháidez, José de Jesús (Instituto de Ecología, A.C., 2016)
Several growth and increment in diameter, height and volume equations were fitted and validated for the pine species Pinus cooperi, P. durangensis, P. engelmannii, P. leiophylla and P. herrerae which naturally distribute in the region of El Salto, Durango, Mexico. The results showed that by using the Chapman-Richards equation the first pine species has the highest growth and increment estimated by two different approaches. This paper points out the need to establish permanent sampling plots to calibrate these technologies to be used in growth and yield modeling at the whole stand, size class or individual tree models.